Interaction of pAsa5 and pAsa8 Plasmids in Aeromonas salmonicida subsp. salmonicida - Pierre-Étienne Marcoux; Sarah B. Girard; Kim C. Fournier; Catherine A. Tardif; Ariane Gosselin; Steve J. Charette (Microorganisms, 2023)
The plasmid known as pAsa5 is present in Aeromonas salmonicida subsp. salmonicida, a fish pathogen. The pAsa5 plasmid carries genes that are essential for the bacterium’s virulence. Recombination events are known to occur in pAsa5, resulting in the loss of certain segments or the acquisition of additional genetic elements. For example, the transposon carried by the large pAsa8 plasmid was found to be inserted into the pAsa5 plasmid in the SHY16-3432 strain, enabling the addition of antibiotic resistance genes to this plasmid, which does not normally possess any. In this study, we present the isolation of additional strains carrying pAsa8. Further analyses of these strains revealed that a fusion between pAsa5 and the complete version of pAsa8 is possible. The pAsa8 transposon insertion in pAsa5 seen in the SHY16-3432 strain appears to be an aberrant event compared to the fusion of the two full-length plasmids. A 22-nucleotide sequence, present in both plasmids, serves as the site for the fusion of the two plasmids. Moreover, it is possible to introduce pAsa8 through conjugation into naive strains of A. salmonicida subsp. salmonicida and once the plasmid is within a new strain, the fusion with pAsa5 is detectable. This study reveals a previously unexplored aspect of pAsa5 plasmid biology, highlighting an additional risk for the spread of antibiotic resistance genes in A. salmonicida subsp. salmonicida.